Polypharmacy in Middle-European Rheumatoid Arthritis-Patients: A Retrospective Longitudinal Cohort Analysis With Systematic Literature Review - Jack, Jacqueline Désirée; McCutchan, Rick; Maier, Sarah; Schirmer, Michael (Frontiers in Medicine, 2020)
Objective: To assess polypharmacy and related medication aspects in Middle-European rheumatoid arthritis (RA) patients, and to discuss the results in view of a systematic literature review. Methods: In this retrospective cohort study, charts were reviewed from RA-patients consecutively recruited between September 27, 2017 and April 29, 2019. Drugs were assigned to the Anatomical Therapeutic Chemical (ATC) groups as proposed by the World Health Organisation (WHO). Results were compared to those of a systematic literature review. Results: 175 consecutive RA-patients were included. The mean number of drugs was 6.6 ± 3.5, with 2.4 ± 1.2 drugs taken specifically for RA – compared to 2.6 in the literature. 33.7% of patients experienced polypharmacy defined by 5 drugs, compared to 61.6 % in the literature - with women affected more frequently than men. After 7 years of follow-up, the number of drugs increased in all ATC-groups by an average of 12.7 %, correlating with age (Corrcoeff= 0.46) and comorbidities (Corrcoeff= 0.599). In the literature, polypharmacy is not always defined precisely, and has not been considered in management guidelines so far. Conclusion: Polypharmacy is a frequent issue in RA-management. With an increasing number of comorbidities during the course of the disease, polypharmacy becomes even more relevant.